Climate Risk Country Profile : Kyrgyz Republic - World Bank Group; Asian Development Bank (World Bank, Washington, DC and Asian Development Bank, Manila, 2021)
The Kyrgyz Republic is bordered by Kazakhstan to the north, Uzbekistan to the west, Tajikistan to the southwest, and China to the east. A wide variety of natural hazards also affect the Kyrgyz Republic. Earthquakes are common and have led to loss of life and significant damage to infrastructure and livelihoods, typically occurring every 5 to 10 years. Climate related hazards are also common and diverse. This document aims to succinctly summarize the climate risks faced by PNG. This includes rapid onset and long-term changes in key climate parameters, as well as impacts of these changes on communities, livelihoods, and economies, many of which are already underway. This is a high-level synthesis of existing research and analyses, focusing on the geographic domain of PNG, therefore potentially excluding some international influences and localized impacts. The core data presented is sourced from the database sitting behind the World Bank Group’s (WBG) climate change knowledge portal (CCKP), incorporating climate projections from the Coupled Model Inter-comparison Project Phase 5 (CMIP5). This document is primarily meant for WBG and Asian Development Bank (ADB) staff to inform their climate actions. The document also aims to direct the reader to many useful sources of secondary data and research.